2014
DOI: 10.24126/jobrc.2014.8.3.352
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Static Magnetic Field on Growth and Biochemical Indices of Five Fungal Genera

Abstract: The effect of static magnetic field (MF) on the growth and biochemical indices of five fungal genera were studied. Exposing the above genera to the northern pole, southern pole and both poles and their influences were compared with the control treatment (without MF energy). The static MF of 10 gauss was applied to the above fungal genera for seven days at 28°C. The effect of static MF energy on the growth of fungal genera on solid media Sabouraud Dextrose Agar (SDA) and Potato Dextrose Agar (PDA) was classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One of the reasons is that the immersion of an alkaline solution was able to remove some nutrient sources for fungi, such as soluble starch and sugars, forming a barren and harsh environment for microorganisms. In addition, because most fungi thrive at slightly acidic pH values of 5.0-6.0 [43], the high pH micro-environment established by the alkali treatment can inhibit the growth of fungi. Liu et al [44] found that the Chao and ACE indexes of the fungal community of saline-alkali soil were significantly lower than those of untreated control samples.…”
Section: Alpha Diversity Analysismentioning
confidence: 99%
“…One of the reasons is that the immersion of an alkaline solution was able to remove some nutrient sources for fungi, such as soluble starch and sugars, forming a barren and harsh environment for microorganisms. In addition, because most fungi thrive at slightly acidic pH values of 5.0-6.0 [43], the high pH micro-environment established by the alkali treatment can inhibit the growth of fungi. Liu et al [44] found that the Chao and ACE indexes of the fungal community of saline-alkali soil were significantly lower than those of untreated control samples.…”
Section: Alpha Diversity Analysismentioning
confidence: 99%
“…In this phase, the fungus has adapted to the new organic nutrients so that it can grow well and enter the exponential stage. The speed of fungal growth is strongly influenced by physical factors and the growing medium, such as pH and nutrient content, as well as environmental conditions, including temperature and humidity (Ali et al, 2017). In addition, the growth speed is also determined by the nutrient content of the growth medium (Basu et al, 2015).…”
Section: Propagation Of the Pathogenic Fungi In The Liquidmentioning
confidence: 99%
“…The shorter the incubation period, the higher the suitability of the host-pathogen. According to Ali et al (2017), the incubation period is influenced by several factors, including the host, environment, and pathogen. The secondary metabolites of P. fluorescens P60 gave better results when combined with the secondary metabolites of T. harzianum T10.…”
Section: Incubation Periodmentioning
confidence: 99%